Analisis Kekuatan Material Pada Poros Mesin Spinner Peniris Minyak Hasil Produk Makanan - Naufal Azhar Al'Afif; Iwan Nugraha Gusniar; Aa Santoso (Department of Electrical Engineering, University of Patria Artha, 2022)
A spinner machine is an oil draining machine that works based on centrifugal force, this tool is equipped with appropriate technology that can reduce the oil content contained in food. The machine can drain cooking oil on food products more easily, quickly, and practically, where the ingredients or food products produced are cleaner and drier than oil or water. The working principle of an oil draining machine is almost the same as the working principle of a washing machine when in the drying process so that the shaft becomes an important element in resisting the rotation that occurs in this draining machine. The purpose of this study is to determine the distribution of the load on the shaft and find the best safety value of the material to be used. The specifications of the shaft used in the form of a pipe have a length of 630 mm, and a diameter of 15 mm, and the planned materials are st37 and ASTM a36 steel. With the results of the analysis value using the 2019 Solidworks software on testing the oil draining spinner machine shaft, the value on the ASTM A36 material with a load of 3 kg obtained a safety value of 3.3. At a load of 10 kg, the safety value is 1.0. And at a maximum load of 20 kg, a safety value of 0.5 is obtained. So that the strongest material that can withstand a load of up to 20 kg is st37 / AISI 1045 steel with a safety value at a load of 3 kg the safety value is 7.9. At a load of 10 kg, the safety value is 2.2. And at a maximum load of 20 kg, the safety value is 1.1. Keywords: axle, spinner machine, design, analysis.